Mal Paharia culture at the crossroad - Sarkar, Amitabha; Dasgupta, Samira (New Delhi : Agam Kala Prakashan, 2011)
Study conducted at Gopikandar and Dumka blocks of Dumka District in Jharkhand, India.
Includes bibliographical references (p. [119]-121) and index.
Keywords: MALTO (INDIC PEOPLE) -- INDIA -- DUMKA (DISTRICT) -- SOCIAL LIFE AND CUSTOMS; DUMKA (INDIA : DISTRICT) -- SOCIAL LIFE AND CUSTOMS